A Systematic Literature Review of Teacher Well-Being in ESD: Integrating Tat Twam Asi as a Humanistic Organizational Value - Brendan Gionino Soesanto; Ida Bagus Adhi Sukma; Ni Made Sukma Anggreni; Adelia Rahmawati Sjaheru; Sri Utari; Yoan Septisari Toelle; Puspito Hadi (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
This study employs a systematic literature review to analyze teacher well-being within the framework of Education for Sustainable Development and examine the integration of the local wisdom value of Tat Twam Asi as a humanistic organizational principle. The review synthesizes findings from reputable scientific journals to identify conceptual developments, influencing factors, and research gaps. The results indicate that teacher well-being in ESD remains largely conceptual and fragmented, with limited integration into sustainable education frameworks, as existing literature predominantly emphasizes student outcomes and pedagogical effectiveness. Teacher well-being is shaped by individual factors, such as self-efficacy and emotional regulation; organizational factors, including workload and institutional support; and pedagogical demands that often lead to role overload. Furthermore, the integration of Tat Twam Asi values serves as a social and moral resource that strengthens empathy, solidarity, and psychological safety thereby supporting the eudaimonic well-being of teachers and contributing to sustainable educational practices.